Base‐Free Asymmetric Transfer Hydrogenation of 1, 2‐Di‐ and Monoketones Catalyzed by a (NH)2P2‐Macrocyclic Iron(II) Hydride. Issue 39 (18th August 2017) - De Luca, Lorena; Mezzetti, Antonio
Abstract: The hydride isonitrile complex [FeH(CNCEt3 )(1 a )]BF4 (2 ) containing a chiral P2 (NH)2 macrocycle (1 a ), in the presence of 2‐propanol as hydrogen donor, catalyzes the base‐free asymmetric transfer hydrogenation (ATH) of prostereogenic ketones to alcohols and the hemihydrogenation of benzils to benzoins, which contain a base‐labile stereocenter. Benzoins are formed in up to 83 % isolated yield with enantioselectivity reaching 95 % ee. Ketones give the same enantioselectivity observed with the parent catalytic system [Fe(CNCEt3 )2 (1 a )] (3 a ) that operates with added NaO t Bu. Abstract : Base? No thanks ! A hydride isonitrile iron(II) complex bearing a C 2 ‐symmetric diamino (NH)2 P2 macrocyclic ligand catalyzes the asymmetric transfer hydrogenation of ketones under base‐free conditions with excellent enantioselectivity (up to 99 % ee ). Base‐labile benzoins are formed from the corresponding benzils with up to 95 % ee .